Takhrij and Syarah Hadith of Chemistry: Uses of Soil in Cleaning Dog Saliva - Intan Purnama Sari; Reimia Ramadana; Ibrahim Syuaib Z; Didi Supandi; Assyifa Junitasari (Gunung Djati Conference Series, 2021)
This study aims to discuss the hadith of the Prophet Muhammadﷺ about the role of soil as one of the materials used to clean dog saliva feces. This research method is qualitative through the approach of takhrij and syarah hadith with chemical analysis. The results and discussion of this research are that since the time of the Prophet until now the soil has been believed as a material used to purify dog ​​saliva, especially with the presence of research through the field of chemistry. This study concludes that the hadith is concluded to be of authentic quality and the truth of the content of the hadith can be proven, that by chemical analysis of the soil has a usefulness that has been tested to be able to clean the feces of dog saliva.